Changes in free polyamine levels, expression of polyamine biosynthesis genes, and performance of rice cultivars under salt stress: a comparison with responses to drought - Do, Phuc T.; Drechsel, Oliver; Heyer, Arnd G.; Hincha, Dirk K.; Zuther, Ellen (Frontiers in Plant Science, 2014)
Soil salinity affects a large proportion of rural area and limits agricultural productivity. To investigate differential adaptation to soil salinity, we studied salt tolerance of 18 varieties of Oryza sativa using a hydroponic culture system. Based on visual inspection and photosynthetic parameters, cultivars were classified according to their tolerance level. Additionally, biomass parameters were correlated with salt tolerance. Polyamines have frequently been demonstrated to be involved in plant stress responses and therefore soluble leaf polyamines were measured. Under salinity, putrescine (Put) content was unchanged or increased in tolerant, while dropped in sensitive cultivars. Spermidine (Spd) content was unchanged at lower NaCl concentrations in all, while reduced at 100 mM NaCl in sensitive cultivars. Spermine (Spm) content was increased in all cultivars. A comparison with data from 21 cultivars under long-term, moderate drought stress revealed an increase of Spm under both stress conditions. While Spm became the most prominent polyamine under drought, levels of all three polyamines were relatively similar under salt stress. Put levels were reduced under both, drought and salt stress, while changes in Spd were different under drought (decrease) or salt (unchanged) conditions. Regulation of polyamine metabolism at the transcript level during exposure to salinity was studied for genes encoding enzymes involved in the biosynthesis of polyamines and compared to expression under drought stress. Based on expression profiles, investigated genes were divided into generally stress-induced genes (ADC2, SPD/SPM2, SPD/SPM3), one generally stress-repressed gene (ADC1), constitutively expressed genes (CPA1, CPA2, CPA4, SAMDC1, SPD/SPM1), specifically drought-induced genes (SAMDC2, AIH), one specifically drought-repressed gene (CPA3) and one specifically salt-stress repressed gene (SAMDC4), revealing both overlapping and specific stress responses under these conditions.